A novel measurement to evaluate supraspinatus tendinopathies with strain elastography. (October 2021) - Özel, Deniz; Demir, Yüksel; Özel, Betül Duran; Adaş, Müjdat
Background: In addition to the traditional strain ratio (STR), a novel measurement termed hard percent of the whole tendon, provided by the device's software and resembling shear-wave elastography, was included in the study. Purpose: To evaluate the correlation between magnetic resonance imaging (MRI) and strain elastography findings in cases with rotator cuff tendinopathy, including tears. Material and Methods: As a prospective study, cases suggestive of rotator cuff tendinopathy were included. After MRI evaluation by two observers, grading of the elastography examination was performed by a third radiologist. For the first measurement, the region of interest (ROI) was chosen from the gray-scale evaluation corresponding to the area showing a MRI pathological signal. Stiffness was assessed with the STR. For the second measurement, the whole visible tendon was measured as the ROI. The hard percent (unaffected areas as a percent) was measured. Correlation coefficients between MRI grade and the two strain value measurements were calculated. Results: There were 93 cases (31 men, 62 women) with 112 involved tendons. The correlation coefficient between MRI grade and age was calculated as 0.56, between MRI grade and STR it was –0.51, and with the novel measurement the correlation coefficient was –0.53. Conclusion: This study showed a good association of findings of tendon stiffness with those of tendinopathy on MRI. Using the hard ratio as a novel measurement, its correlation with MRI grade was as reliable as the STR. We also experienced that the benefit of elastography is a challenging issue for defining small ruptures.